Single molecule fate of HIV-1 envelope reveals late-stage viral lattice incorporation - Carmen A. Buttler (Nature Portfolio, 2018)
HIV particles contain a relatively low amount of viral envelope (Env), but underlying packaging mechanisms are poorly understood. Here, the authors use superresolution microscopy and show that Env distribution is biased toward the necks of cell-associated particles during assembly.